Relación entre el test estresante y la asfixia neonatal de los recién nacidos Hospital Regional Docente De Trujillo, 2021-2022 - Corcuera Murillo, Jhery Geraldine (2025)
In order to determine the relationship between the Stress Test and Neonatal Asphyxia of newborns at the Trujillo Regional Teaching Hospital. La Libertad.2021-2022, an explanatory relationship design research was carried out in a sample of 96 clinical histories that met the inclusion criteria; the data was collected through a form. It was found that 5.2% of pregnant women monitored through the stress test with a positive result and 96% of pregnant women with a negative stress test. Newborns with neonatal asphyxia were 6.3% and without asphyxia 93.8%. It is concluded that there is a relationship between the Stress Test and Neonatal Asphyxia of newborns (p-value < 0.01)